IMPACT ANALYSIS OF BOLT-CLAMPING FORCE TO FILLED-HOLE LAMINATES INTERLAMINAR STRESS - CAO Yong; FENG YunWen; XUE XiaoFeng; ZHU XianFei (Jixie qiangdu)
Using composite laminates with a bolt-filled hole were proposed to study interlaminar stress distribution of laminates joints hole-edge,and a 3D finite element model with a zero-thickness cohesive element was established for solving holeedge interlaminar stress of laminated plate in tension.The results show that interlaminar normal stress distribution along the hole mainly affected by the bolt-clamping force,under the same bolt-clamping force,interlaminar normal stress value ranges is close;The interlaminar shear stress impact both by the bolt-clamping force and interface ply parameters,such as interlaminar shear stress of [-45 /90] and [0 /-45] interface is larger than others; Interlaminar normal stress caused by bolt-clamping force was mainly compressive stress,and it is beneficial for the interlaminar strength,but interlaminar shear stress generated in the same time is not help to improve the interlaminar strength,therefore,a reasonable clamping force can enhance the interlaminar strength for bolt composite joints.